Obecność form dokumentalnych w polskiej literaturze pięknej realizmu socjalistycznego - Mazurkiewicz, Adam (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2012)
The article is dedicated to ways in which authors of the socialist realism novel used the poetics of the non-fiction literature (mainly reportage). Perceiving a work of art as a cultural fact of political character had serious consequences. The literary creation was to be replaced by a reportage storyline. The outer reality was depicted in accordance with top-down guidelines of propaganda. Two strategies were used: linking poetics of documentary with belles lettres and incorporating elements typical of non-fiction literature to fiction.At the same time genological “light-heartedness” of authors of socialist realism makes it now difficult to decide about typological affiliation of those works.